Screen success at US WWTP. Issue 5 (September 2019) - Unknown
Abstract : The Hyperion water reclamation plant (WRP) in Los Angeles is one of the most advanced wastewater treatment plants in the world. When the old screens were upgraded, it chose an international wastewater treatment specialist to provide new screening equipment.